2020
DOI: 10.1080/07391102.2020.1850352
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin: a bioactive metabolite of C ordyceps militaris and polyadenylation inhibitor with therapeutic potential against COVID-19

Abstract: Spike protein and main proteases of SARS-CoV-2 have been identified as potential therapeutic targets and their inhibition may lead to the reticence of viral entry and replication in the host body. Despite several efforts; till now no specific drugs are available to treat SARS-CoV-2. Considering all these challenges, the main objective of the present study was to establish therapeutic potential of cordycepin against COVID-19 as a conventional therapeutic strategy. In the present study; molecular interaction stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
(64 reference statements)
0
28
0
Order By: Relevance
“…Cordycepin is a promising potential comprehensive anti-COVID-19 agent that should be put under the microscope in the coming days. Some new studies reported the in silico inhibitory activities of cordycepin on SARS-CoV-2 spike (S) protein and main protease (M pro ) enzyme, 46 , 56 , 57 and, recently, another computational study showed the in silico inhibitory activities of cordycepin on the SARS-CoV-2 RdRp enzyme. 47 In light of the findings of the previous in silico studies and the current in vitro study, it is proven that the cordycepin molecule has interesting superiority and advantage over most of the other investigational anti-SARS-CoV-2 molecules, especially those acting only on the S protein and/or M pro enzyme, as, first, it acts via the expected synergistic triple anti-SARS-CoV-2 mode of action ( i.e.…”
Section: Conclusion and Future Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cordycepin is a promising potential comprehensive anti-COVID-19 agent that should be put under the microscope in the coming days. Some new studies reported the in silico inhibitory activities of cordycepin on SARS-CoV-2 spike (S) protein and main protease (M pro ) enzyme, 46 , 56 , 57 and, recently, another computational study showed the in silico inhibitory activities of cordycepin on the SARS-CoV-2 RdRp enzyme. 47 In light of the findings of the previous in silico studies and the current in vitro study, it is proven that the cordycepin molecule has interesting superiority and advantage over most of the other investigational anti-SARS-CoV-2 molecules, especially those acting only on the S protein and/or M pro enzyme, as, first, it acts via the expected synergistic triple anti-SARS-CoV-2 mode of action ( i.e.…”
Section: Conclusion and Future Recommendationsmentioning
confidence: 99%
“…, acts as a polyadenylation inhibitor), severe shortening of poly(A) tails, continuous destabilization of mRNAs, strong purine biosynthesis inhibition, and also premature termination of protein synthesis. 33 , 36 , 46 …”
Section: Introductionmentioning
confidence: 99%
“…This mushroom inhibited viral-induced membrane fusion, and could act against the early stages of HSV viral infection. The aqueous extracts of I. obliquus could prevent HSV-1 entry by directly acting on viral glycoproteins, which in turn prevent membrane fusion [ 321 ]. With a host of accomplishments against various reputed viruses, IO does stand a chance against COVID, yet has a long way to go.…”
Section: Antiviral Activity Of Mushrooms/mushroom Polysaccharidesmentioning
confidence: 99%
“…Verma et al, studied the molecular interaction between cordycepin, a key component of Cordyceps sinensis , and novel coronavirus-related target protein by molecular dynamics simulation, and found that cordycepin had strong binding force with RBD domain of novel coronavirus spike protein. This suggests that cordycepin may be used as a pan coronavirus fusion inhibitor targeting spike proteins to limit the entry of the virus into the body [ 17 ].…”
Section: Antiviral Activitymentioning
confidence: 99%